Estudio e implementación en Python de un modelo para el Memristor de Hewlett Packard (2022)
The memristor is the fourth element that completes the cycle of the variables of an electric circuit, it is passive with two terminals and nonfour fundamental linear, since it directly relates the electric charge with the magnetic flux. The physical realization in the laboratories of Hewlett Packard in 2008 was a very imp ortant advance for electronics, since with this the theory of Leon Chua was demonstrated at the time. In this work, the development of a simulated model for the Hewlett Packard Memristor is exposed, which is implemented in Python, initially making an und erstanding of the mathematical model used in Hewlett Packard and its implementation with a code in Python and carrying out an evaluation. , analysis and comparison of the results with respect to the base model, demonstrates the veracity and effectiveness o f the model